The Effect of Corporate Social Responsibility Disclosure, Financial Performance, and Firm Size on Stock Returns - Ni Putu Diah Iswari; I Nyoman Wijana Asmara Putra (Harmony Management: International Journal of Management Science and Business, 2025)
Stock returns represent a crucial parameter that serves as a reference for investors in evaluating company performance. A decline in returns has occurred in several mining companies listed on the IDX, despite the sector’s vital role in the national economy. This study aims to examine the effect of Corporate Social Responsibility (CSR), Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Firm Size on the stock returns of mining companies listed on the IDX during the 2022–2024 period. The sample was determined using purposive sampling, resulting in 56 observational data after outliers were removed. To meet the assumptions of classical tests, several variables were transformed using natural logarithms, and data were analyzed using multiple linear regression. The results indicate that CSR, ROE, and Firm Size have no significant effect on stock returns, whereas ROA and DER show a significant positive effect. These findings suggest that investors tend to emphasize financial fundamentals, particularly profitability and capital structure, rather than non-financial aspects such as CSR activities. The implication for companies is the need to enhance operational efficiency and optimize financial structures to attract investors and improve returns. Future researchers are encouraged to incorporate external variables such as global commodity prices, market risk, and macroeconomic indicators, as well as expand the observation period and apply more diverse methodological approaches to provide a more comprehensive understanding of stock return dynamics in the mining sector.